School leadership and teacher professional development in Lesotho : a case study of two secondary schools in Leribe District. - Letsatsi, Setungoane (My University, 2010)
This study investigates the role of leadership in teacher professional development in Lesotho high schools. The specific variables being investigated include teachers‟ perceptions of teacher professional development; their expectations as well as the principals‟ role in facilitating teacher professional development. Developments in leadership have led to changes in the ways teachers work. These have subsequently increased the need to review teacher professional development programmes as a means to enhance teachers‟ competences and to determine their appropriateness to their work Green (1999) in Blandford (2000) argues that professional development has now become a prerequisite to effective schools. In his view, effective schools don‟t just happen; they thrive because the people in them work hard to make them successful. Blandford (2000) emphasises this in stating that, “in order [for schools] to be effective, managers and teachers will need to engage in professional development.” One of the most influential links to accurate teacher professional development is the active involvement of principals in such initiatives. The objective of this research is to establish how the dual responsibility of the principal and the teachers manifests itself in professional development. So while, the principal is expected to take a lead role, both are expected to take an active part if professional development is to have any impact in their teaching and learning - the core business of schools. Even though, it is very important to know teachers‟ perceptions on the link between leadership and teacher professional development, this is one of the few researches carried out on how leadership contributes to teacher development, This research is iii therefore significant as it examines the voices of teachers on how leadership contributes to teacher professional development. In Lesotho, there is a problem of limited understanding of professional development by teachers and the schools in general. The research was conducted using qualitative methodology. It was based on a case study of two high schools in the Leribe district in Lesotho. Data was collected using questionnaires and follow up interviews which were administered to elicit responses from principals, deputy principals and teachers in both schools. The findings revealed a need for teachers in Lesotho to engage more in teacher professional development programmes so that they may have a better understanding of the concept. Their understanding at the time did not go beyond workshops or at the most induction programmes that are provided at the beginning of their careers. This study also demonstrated that teacher professional development should be core to the work of both the principals and teachers in order to create a learning environment in their schools where both can develop professionally. In addition to this, teachers should be encouraged to initiate some of the professional development activities that can only be accessed if they show willingness. This is consistent with Blandford (2000:4), who asserts that the effective management of professional development depends on individual enthusiasm, not compulsion, and on individuals prepared to take action in addressing their own professional needs. What also emerged as one of the key findings was that teachers felt that principals should take more responsibility in reinforcing the culture of professional development in schools. iv Based on the results obtained in this study, the results suggest that schools in Lesotho need more awareness in teacher professional development and how it is influenced by leadership. There is an overarching need for a properly functioning policy that would guide the implementation of teacher professional development activities both from outside and within the school.
Keywords: Leadership; Principals; Teachers; Teacher professional development; Teaching and learning